2018
DOI: 10.1111/imj.14120
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar spine fusion: what is the evidence?

Abstract: Lumbar spine fusion is a common procedure associated with a high cost burden and risk of serious complications. We aimed to summarise systematic reviews on the effectiveness of lumbar spine fusion for most diagnoses. We found no high‐quality systematic reviews and the risk of bias of the randomised controlled trials in the reviews was generally high. The available evidence does not support a benefit from spine fusion compared to non‐operative alternatives for back pain associated with degeneration. The availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 34 publications
1
49
0
1
Order By: Relevance
“…This is supported by a 2019 systematic review (14 studies) which found evidence that imaging is associated with higher medical costs, increased health care utilization and more work absence compared with nonimaged groups. 61 Despite little evidence to support its use for most back conditions, 43 and a 20% failure rate, 91 another US study estimated that $US12.8billion was spent on spinal fusion surgery in 2011, the highest aggregate hospital costs of any surgical procedure. 92…”
Section: Many Patients With Low Back Pain Are Still Receiving the mentioning
confidence: 99%
“…This is supported by a 2019 systematic review (14 studies) which found evidence that imaging is associated with higher medical costs, increased health care utilization and more work absence compared with nonimaged groups. 61 Despite little evidence to support its use for most back conditions, 43 and a 20% failure rate, 91 another US study estimated that $US12.8billion was spent on spinal fusion surgery in 2011, the highest aggregate hospital costs of any surgical procedure. 92…”
Section: Many Patients With Low Back Pain Are Still Receiving the mentioning
confidence: 99%
“…For example, some in the back pain field dismiss the label non‐specific low back pain and instead argue for labels targeting a specific structure (disc, facet joint) or mechanism (eg instability) and the use of similarly targeted personalized therapies. The problem is that the diagnoses offered are nominal diagnoses that drive more invasive, costly and ineffective therapies without providing benefit . The resulting overuse is substantial: for example the most expensive surgical procedure (US$12.8 billion per annum) in the USA is spine fusion, a procedure that is most commonly performed for degenerative conditions for which there is good evidence of harm and poor evidence of benefit over cheaper and safer alternatives.…”
Section: Overdefinitionmentioning
confidence: 99%
“…magnetic resonance imaging) had increased over 21 years 7 . There is no robust evidence of benefit for spinal fusion surgery compared with non-surgical care for people with low back pain associated with spinal degeneration 8 . However, over the years 2004–2015, elective spinal fusion surgery in the United States increased by 62.3% (from 60.4 per 100 000 to 79.8 per 100 000), with hospital costs for this procedure exceeding 10 billion United States dollars (US$) in 2015 9 .…”
Section: Introductionmentioning
confidence: 99%